Aqueous ion battery, pole piece assembly and preparation method of pole piece assembly

By optimizing the combination of pole sheet material and current collector, the pole sheet assembly with pore gradient is prepared, which solves the problems of performance and stability of aqueous sodium ion batteries, and achieves higher energy density and cycle stability. It is suitable for electric vehicles. and energy storage.

CN119170730APending Publication Date: 2024-12-20VERENA ENERGY GROUP PTE LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411313896.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing aqueous sodium ion batteries have problems such as low energy density, poor circulation stability and poor adhesion of the electrode sheet material to the current collector, which limits their performance and application range.

Method used

By optimizing the particle size ratio, binder content and carbon-containing material coating of the electrode sheet material, an electrode sheet assembly with a porosity gradient is prepared, and the electrode sheet material is firmly bonded to the carbon material through high-temperature rolling technology to enhance the collection The contact area and bonding effect of the fluid to the pole sheet.

Benefits of technology

提高了极片的均一性和导电性,增强了电池的安全性、环保性和热稳定性,降低了起火和爆炸风险,提升了能量密度和循环寿命,适用于高温及低温环境。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170730A_ABST
    Figure CN119170730A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aqueous ion batteries, and particularly discloses an aqueous ion battery, a pole piece assembly and a preparation method of the pole piece assembly. The aqueous ion battery pole piece assembly comprises a battery pole piece and a current collector with a carbon material coating, the pole piece is attached to the current collector through high-temperature rolling, and a pole piece material is firmly bonded with the carbon material coating, wraps the outer side of the current collector, is of a three-dimensional contact structure and has a good contact interface and conductivity; the electrode plate has porosity gradient, so that the electrochemical active area and the ion transmission rate of the electrode are improved; the current collector material is lengthened and cut to reserve the tabs, and the tabs do not need to be welded additionally. The aqueous ion battery has the advantages of simple structure, good contact of the pole piece assembly, no need of additional pressure application to attach battery devices, improvement of the structural stability, improvement of the electrochemical performance and the cycle stability of the battery, and wide application to preparation of ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aqueous ion batteries, and in particular relates to an aqueous ion battery, a pole piece assembly and a preparation method thereof. Background Art

[0002] At present, lithium-ion batteries, as the most commonly used secondary batteries, have been widely used in various electronic products, electric vehicles and energy storage fields. However, the scarcity and price fluctuations of lithium resources have made researchers look for alternatives. Sodium-ion batteries are considered to be a potential alternative due to their abundant sodium resources, low cost and environmental friendliness. Most existing sodium-ion batteries use organic electrolytes, which have problems such as flammability, toxicity and environmental pollution. In addition, the thermal stability and electrochemical stability of organic electrolytes are relatively low, which limits the application of sodium-ion batteries in high or low temperature environments. Therefore, it is of great significance to develop a safe, environmentally friendly and stable aqueous sodium-ion battery. Aqueous sodium-ion batteries have attracted widespread attention due to their safety, environmental protection and stability. However, traditional aqueous sodium-ion batteries have problems such as low energy density and poor cycle stability, which limit their wide application. Among them, the current collector is one of the important factors affecting the performance of aqueous sodium-ion batteries. Existing aqueous sodium-ion battery current collectors mainly include carbon paper and copper foil. Carbon paper has good conductivity, but relatively low mechanical strength and stability; copper foil has high mechanical strength and stability, but relatively low conductivity. Therefore, it is necessary to improve the current collector material to improve the performance of aqueous sodium-ion batteries. The existing aqueous sodium-ion battery preparation process still has some problems, such as poor adhesion between the electrode material and the current collector, poor electrode porosity, poor electrode uniformity, etc., which affect the performance of the battery. Therefore, it is necessary to improve the electrode preparation process in combination with the current collector and the electrode to improve the performance of aqueous sodium-ion batteries. Summary of the invention

[0003] The main purpose of the present invention is to overcome the shortcomings of the prior art and provide an aqueous ion battery, a pole piece assembly and a preparation method thereof, so as to optimize the pole piece porosity structure, improve the pole piece uniformity, and improve the bonding effect, conductivity and stability of the pole piece material.

[0004] To achieve the above object, the present invention provides a method for preparing an aqueous ion battery electrode assembly, comprising the following steps:

[0005] Select materials with different particle sizes, mix the selected materials with different particle sizes, maintain different particle size ratios, adjust the binder content, stir and disperse the mixed materials, and respectively prepare rollable material agglomerates, wherein the particle size range is 1-75 μm;

[0006] The material lumps are respectively pressed into pole pieces by a roller press to obtain a series of pole piece layers with different porosity formulas;

[0007] The preheated current collector with carbon material coating is sandwiched into the pole sheet layer with the highest porosity formula and rolled at high temperature to obtain a battery pole sheet assembly with a single-layer pole sheet layer wrapped around the current collector under a certain pressure and temperature, and the pole sheet material and the carbon material coating are firmly bonded;

[0008] A series of electrode layers with different porosity formulas are sequentially clamped to the outside of a battery electrode assembly with a single or multiple electrode layers wrapped with a current collector in a sheet-like structure in the order of the porosity formula from high to low, and rolled to obtain a battery electrode assembly with a electrode wrapped with a current collector having a porosity gradient;

[0009] Drying the prepared battery pole piece assembly at a certain temperature to remove solvent and moisture;

[0010] Apply pressure to the dry electrode and perform high-temperature hot pressing to make the electrode layer tighter.

[0011] Preferably, the current collector material includes one or more of stainless steel, nickel, titanium, aluminum, zinc, copper or carbon fiber, and the morphology includes mesh or foil, with a thickness of 5 μm to 1 mm.

[0012] Preferably, the method of coating the carbon material coating on the current collector includes one or more of blade coating, spray coating or spin coating, and the carbon-containing mixed slurry used in the coating includes carbon material, binder, conductive additive and solvent; the carbon material is graphene or graphite, the binder includes polyacrylate or polytetrafluoroethylene, the conductive additive includes carbon nanotubes or conductive black, the solvent includes N-methylpyrrolidone or deionized water, and the thickness of the carbon material coating is 10 to 2000 μm.

[0013] Preferably, the mass percentages of the raw material components of the pole piece material are: 60% to 92% of the active material, 4% to 15% of the binder, and 5% to 20% of the conductive agent; wherein the active material is one or more of the plasma deintercalation compounds of transition metal oxides containing lithium / sodium; the binder is selected from at least one of polytetrafluoroethylene, polyacrylate, polyethylene oxide, polyacrylonitrile, polyimide, polyester, fluorinated polymer, polydivinyl polyglycol, polyethylene glycol diacrylate, and polyethylene glycol dimethacrylate; the conductive agent is selected from at least one of activated carbon, acetylene black, carbon black, graphite, carbon fiber, carbon nanotubes, graphene, and mixed conductive slurries thereof.

[0014] Preferably, the thickness of each pole piece layer is 0.3-3 mm, the total thickness of the pole piece is 0.5-6 mm, and the density is 0.6-1.5 g / cm 3 .

[0015] Preferably, the specific conditions during rolling include: rolling temperature of 20-220° C.; roll gap of 0.3-6 mm; roll speed of 0.1-10 m / min; and the number of rolling times of at least 6 times.

[0016] Preferably, the current collector and the electrode tab are an integrated structure, and there is no need to weld the electrode tab separately.

[0017] Preferably, the contact area between the current collector and the pole piece material is 85%-100%.

[0018] A water-based ion battery pole piece assembly prepared according to any of the above methods, comprising a battery pole piece and a current collector, wherein the current collector is a substrate coated with a carbon-containing material coating on the surface, the pole piece and the current collector are bonded together by high-temperature rolling, the pole piece material and the carbon material coating are firmly bonded and wrapped around the outside of the current collector, forming a three-dimensional contact integrated structure; the battery pole piece assembly is a sheet structure with a porosity gradient, composed of several pole piece layers with different porosities, and the porosity of the pole piece layer is controlled by adjusting the material particle size and the binder content.

[0019] An aqueous ion battery is a soft-pack battery with a positive electrode plate assembly-diaphragm-negative electrode plate assembly structure, wherein the plate assembly is prepared by any of the above methods, the electrolyte is a (0.3-2.0) mol / L sodium sulfate solution or lithium sulfate solution or a mixed solution of the two, the diaphragm is one of glass fiber, filter paper, non-woven fabric, and weighing paper, and the assembled battery does not require external pressure-maintaining facilities.

[0020] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0021] (1) The process for preparing the integrated pole piece assembly structure of an aqueous ion battery of the present invention optimizes the porosity structure of the pole piece, improves the uniformity of the pole piece, and improves the bonding effect between the current collector and the pole piece material by optimizing the ratio and porosity gradient of the pole piece material, the ratio and coating method of the carbon-containing material coating slurry, and the carbon-containing material coating current collector and pole piece hot pressing conditions, thereby improving the performance of the aqueous sodium ion battery.

[0022] (2) The aqueous ion battery of the present invention has high safety, reduces the risk of battery fire and explosion, is non-toxic, pollution-free, environmentally friendly, conforms to the concept of green development, and has good thermal stability and electrochemical stability, which is conducive to the application of the battery in high and low temperature environments.

[0023] (3) The aqueous ion battery of the present invention improves energy density, cycle life and cycle stability while maintaining safety, environmental protection and stability. Therefore, the aqueous ion battery of the present invention can be widely used in electric vehicles, energy storage, communication base stations and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the front structure of the integrated pole piece (positive or negative electrode) assembly structure of the present invention;

[0025] Figure 2 It is a schematic diagram of the side structure of the integrated pole piece (positive or negative electrode) assembly structure of the present invention;

[0026] Figure 3 It is a schematic diagram of the top view of the integrated pole piece (positive or negative electrode) assembly structure of the present invention;

[0027] Figure 4 The SEM microscopic morphology of the surface-coated carbon material coating current collector prepared by the present invention;

[0028] Figure 5 The figure is a comparison of the charge and discharge cycle performance of the batteries prepared in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION

[0029] The technical scheme of the present invention is further described below by specific implementation methods. The embodiments described herein are only to help understand the present invention and should not be regarded as specific limitations of the present invention. The described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professionals and technicians in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by publicly known methods.

[0030] Example:

[0031] The positive electrode material formula is as follows: the electrode layer 1 is Na with a mass fraction of 85%. 0.44 MnO 2 (NMO) powder, 5% carbon black and 10% PTFE binder, the pole layer 2 is 86.8% NMO powder, 5.2% carbon black and 8% PTFE binder, the pole layer 3 is 88.6% NMO powder, 5.4% carbon black and 6% PTFE binder, the pole layer 4 is 90.4% NMO powder, 5.6% carbon black and 4% PTFE binder, the particle size of NMO material in pole layer 1 to 4 decreases successively Specifically, the particle size of the NMO material in the pole layer 1 is 25-75μm, the particle size of the NMO material in the pole layer 2 is 10-50μm, the particle size of the NMO material in the pole layer 3 is 5-25μm, and the particle size of the NMO material in the pole layer 4 is 1-10μm. The porosity of the pole layers 1 to 4 decreases, and the electrolyte wettability becomes worse, but the specific surface area increases, the electrochemical performance of the active material increases, and the overall uniformity of the pole piece is good; the formula of the negative electrode material is as follows: the pole layer a is NaTi with a mass fraction of 85% 2 (PO 4) 3 @C powder, 5% carbon black and 10% PTFE binder, the pole layer b is 86.8% NaTi 2 (PO 4 ) 3 @C powder, 5.2% carbon black and 8% PTFE binder, the pole layer c is 88.6% NaTi 2 (PO 4 ) 3 @C powder, 5.4% carbon black and 6% PTFE binder, the pole layer d is 90.4% NaTi 2 (PO 4 ) 3 @C powder, 5.5% carbon black and 4% PTFE binder, NaTi 2 (PO 4 ) 3 @C Powder particle size decreases in sequence. Specifically, NaTi in the electrode layer a 2 (PO 4 ) 3 @C powder particle size is 25-75μm, NaTi in the pole layer b 2 (PO 4 ) 3 @C powder particle size is 10-50μm, NaTi in the pole layer c 2 (PO 4 ) 3 @C powder particle size is 5-25μm, NaTi in the pole layer d 2 (PO 4 ) 3 @C The powder particle size is 1-10μm, the porosity of the electrode layers a~d decreases, and the specific surface area increases; the positive electrode active material, negative electrode active material, and carbon black are weighed according to the positive and negative electrode material formulas and put into the mixer for high-speed mixing. The mixed powder, PTFE emulsion and 40% deionized water solvent are added to the mixer for mixing. The mixed material lumps are rolled on a roller press to obtain pole pieces, and the preheated carbon material coated current collectors are sandwiched into the pole piece layers 1 and a for high-temperature pressing, and then sandwiched into the pole piece layers 2~4 and b~d in turn for pressing. After drying, high-temperature hot pressing is performed again to obtain the positive and negative electrode integrated pole piece assembly structure. Please refer to Figure 1-3 , the surface microstructure of the current collector coated with carbon material is as follows Figure 4 The prepared pole piece assembly structure and glass fiber separator were assembled into an aqueous ion battery in the order of positive pole piece assembly structure → separator → negative pole piece assembly structure, and a 1.2 mol / L sodium sulfate solution was added to prepare an aqueous ion battery.

[0032] Comparative Example:

[0033] The positive electrode material formula is 87.7% NMO powder, 5.3% carbon black and 7% PTFE binder; the negative electrode material formula is 87.7% NaTi 2 (PO 4 ) 3 @C powder, 5.3% carbon black and 7% PTFE binder; weigh the positive electrode active material, negative electrode active material and carbon black according to the positive and negative electrode material formula and put them into the mixer for high-speed mixing. The mixed powder, PTFE emulsion and 40% deionized water solvent are added to the mixer for mixing. The mixed material mass is rolled on a roller press to obtain a pole piece. The prepared pole piece, the current collector containing the carbon material coating and the glass fiber diaphragm are assembled into an aqueous ion battery in the order of current collector → positive pole piece → diaphragm → negative pole piece → current collector, and a 1.2 mol / L sodium sulfate solution is added to prepare an aqueous ion battery.

[0034] The difference between the embodiment and the comparative example lies in whether the pole piece and the current collector are an integrated pole piece assembly structure, whether the pole piece has a porosity gradient, and the other parameters remain the same.

[0035] The batteries prepared in the examples and comparative examples were tested and cycled at a rate of 0.2C. After 100 cycles of normal cycling, the capacity retention rate of the example was 98.42% of the first cycle discharge capacity, which showed a good capacity retention rate. The charge and discharge cycle performance was as follows: Figure 5 Compared with the battery of the comparative example, the specific capacity, coulombic efficiency and capacity retention rate of the whole battery of the battery of the embodiment are significantly improved, and the battery performance is improved.

Claims

1. A method for preparing an aqueous ion battery electrode assembly, characterized in that: The following steps are involved: Select materials with different particle sizes, mix the selected materials with different particle sizes, maintain different particle size ratios, adjust the binder content, stir and disperse the mixed materials, and respectively prepare rollable material agglomerates, wherein the particle size range is 1-75 μm; The material lumps are respectively pressed into pole pieces by a roller press to obtain a series of pole piece layers with different porosity formulas; The preheated current collector with carbon material coating is sandwiched into the pole sheet layer with the highest porosity formula and rolled at high temperature to obtain a battery pole sheet assembly with a single-layer pole sheet layer wrapped around the current collector under a certain pressure and temperature, and the pole sheet material and the carbon material coating are firmly bonded; A series of electrode layers with different porosity formulas are sequentially clamped to the outside of a battery electrode assembly with a single or multiple electrode layers wrapped with a current collector in a sheet-like structure in the order of the porosity formula from high to low, and rolled to obtain a battery electrode assembly with a electrode wrapped with a current collector having a porosity gradient; Drying the prepared battery pole piece assembly at a certain temperature to remove solvent and moisture; Apply pressure to the dry electrode and perform high-temperature hot pressing to make the electrode layer tighter.

2. The method according to claim 1, characterized in that The current collector material includes one or more of stainless steel, nickel, titanium, aluminum, zinc, copper or carbon fiber, and the morphology includes mesh or foil, with a thickness of 5 μm to 1 mm.

3. The method according to claim 1, characterized in that The method of coating the carbon material coating on the current collector includes one or more of blade coating, spray coating or spin coating, and the carbon-containing mixed slurry used in the coating includes carbon material, binder, conductive additive and solvent; the carbon material is graphene or graphite, the binder includes polyacrylate or polytetrafluoroethylene, the conductive additive includes carbon nanotubes or conductive black, the solvent includes N-methylpyrrolidone or deionized water, and the thickness of the carbon material coating is 10 to 2000 μm.

4. The method according to claim 1, characterized in that: The mass percentages of the raw material components of the pole piece material are as follows: 60% to 92% of the active material, 4% to 15% of the binder, and 5% to 20% of the conductive agent; wherein the active material is one or more of the plasma deintercalation compounds of transition metal oxides containing lithium / sodium; the binder is selected from at least one of polytetrafluoroethylene, polyacrylate, polyethylene oxide, polyacrylonitrile, polyimide, polyester, fluorinated polymer, polydivinyl polyglycol, polyethylene glycol diacrylate, and polyethylene glycol dimethacrylate; the conductive agent is selected from at least one of activated carbon, acetylene black, carbon black, graphite, carbon fiber, carbon nanotubes, graphene, and mixed conductive slurries thereof.

5. The method according to claim 1, characterized in that The thickness of each pole piece layer is 0.3-3 mm, the total thickness of the pole piece is 0.5-6 mm, and the density is 0.6-1.5 g / cm3.

6. The method according to claim 1, characterized in that The specific conditions during rolling include: rolling temperature of 20-220° C.; roll gap of 0.3-6 mm; roll speed of 0.1-10 m / min; and the number of rolling times of at least 6 times.

7. The method according to claim 1, characterized in that The current collector and the tab are an integrated structure, and there is no need to weld the tab separately.

8. The method according to claim 1, characterized in that The contact area between the current collector and the pole piece material is 85%-100%.

9. An aqueous ion battery electrode assembly prepared according to any one of claims 1 to 8, characterized in that: It includes a battery pole piece and a current collector, wherein the current collector is a substrate coated with a carbon-containing material coating on the surface, the pole piece and the current collector are bonded together by high-temperature rolling, the pole piece material and the carbon material coating are firmly bonded and wrapped around the outside of the current collector, forming a three-dimensional contact integrated structure; the battery pole piece assembly is a sheet structure with a porosity gradient, and is composed of several layers of pole piece layers with different porosities, and the porosity of the pole piece layer is controlled by adjusting the material particle size and the binder content.

10. An aqueous ion battery, characterized in that: It is a soft-pack battery with a positive electrode plate assembly-diaphragm-negative electrode plate assembly structure, wherein the plate assembly is prepared by the method of any one of claims 1 to 8, the electrolyte is a (0.3-2.0) mol / L sodium sulfate solution or lithium sulfate solution or a mixed solution of the two, the diaphragm is one of glass fiber, filter paper, non-woven fabric, and weighing paper, and the assembled battery does not require external pressure-maintaining facilities.